Diversity of fungi as human pathogen - Chowdhry, P N; Gupta, Suman Lata; Anand, Nidhi (Recent Research in Science and Technology, 2013)
Worldwide human pathogenic fungi cause I nvasive diseases, pose a serious and growing health problem and are a major cause of death. Superficial mycosis is more prevalent in tropical and subtropical countries including India, where heat and moisture play an important role in promoting of Anthropophilic dermatophytes and tends to get worse during summer, with symptoms alleviating during the winter. Such fungi are known as Dermatophytes and usually colonize the outer layer of the skin, occasionally invade subcutaneous tissues, resulting in kerion development of ringworm symptoms. These symptoms develop by a number of different fungal species e.g. Trichophyton , Microsporum and Epidermatophyton are proved most common causative agents. Such fungi attack various parts of the body and lead to Dermatophytosis as Tinea pedis (athlete's foot) affects on the feet; Tinea unguium on the fingernails and toenails; Tinea corporis on the arms, legs and trunk, Tinea cruris (jock itch) groin area ; Tinea manuum hands and palm area ,Tinea capitis on the scalp, Tinea barbae affects facial hair; Tinea faciei on the face etc.. The other superficial mycoses (not classic ringworm or dermatophytes) are Tinea versicolor caused by Malassezia furfur and Tinea nigra caused by Hortaea werneckii.